Wood chip fiber compaction plate and quantitative production method thereof

Through wet mixing process and high-circular heating and pressurization treatment, combined with the synergistic flame retardant effects of magnesium oxide and magnesium chloride, the problem of difficult to take into account both physical processing and flame retardant performance of broken wood hot-pressed sheets is achieved, and the compression density of broken wood fibers is achieved Quantitative production and performance improvement of boards.

CN119427493APending Publication Date: 2025-02-14王凯
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202411528006.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to take into account the physical processing performance and flame retardant properties of broken wood hot-pressed sheets, and it is also difficult to achieve mass production and cost control.

Method used

Using the wet mixing process, lime milk is mixed with crushed wood fiber powder and then added to resin particles. Through high-circuit heating and pressurization treatment, combined with the synergistic flame retardant effects of magnesium oxide and magnesium chloride, it is prepared with excellent physical properties and flame retardant. Performance crushed wood fiber sealing plate.

Benefits of technology

The quantitative production of crushed wood fiber compact panels has been achieved, and the physical properties and flame retardant properties of the board have been significantly improved, especially in terms of uniformity of nail grip force and flame retardant properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to a quantitative production method of a crushed wood fiber compaction plate. The method comprises the following steps: uniformly stirring 55-80 parts by weight of crushed wood fiber powder and 40-60 parts by weight of lime milk to obtain a primary crushed wood fiber mixture; uniformly mixing the primary wood fiber mixture with 8-12 parts by weight of resin particles to obtain a secondary wood fiber mixture; the secondary wood fiber mixture is placed in a mold to be formed, a wood fiber prefabricated plate is obtained after demolding, and the wood fiber prefabricated plate is subjected to high-frequency heating and pressurizing treatment to obtain a wood fiber compaction plate semi-finished product; and cooling and curing the semi-finished product of the wood chip fiber compaction plate to obtain the wood chip fiber compaction plate. 20-40 parts by weight of magnesium oxide and 3-5 parts by weight of magnesium chloride can also be added into the secondary wood chip fiber mixture to obtain the wood chip fiber compaction plate with flame retardant property. According to the quantitative production method disclosed by the invention, the crushed wood fiber compaction plate with excellent physical property and flame retardant property can be quantitatively produced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hot-pressed wood chip boards, and in particular relates to a wood chip fiber compacted board and a quantitative production method thereof. Background Art

[0002] Chip hot-pressed board can make good use of various types of wood chips. In addition to the advantage of low cost, it is also valued by log board manufacturers that produce a large amount of wood chips based on the consideration of making the best use of wood. Due to the use of additives, the chip hot-pressed board can bring sound insulation, heat insulation, moisture resistance, anti-corrosion and mildew resistance, and fire retardant properties by adjusting the additives. Among them, the chip hot-pressed board with fire retardant properties has the widest application range. However, in the prior art, it is difficult to take into account both physical processing properties and flame retardant properties on the one hand, and mass production and cost on the other hand. In a series of Chinese patent technologies named "high-frequency compaction technology", Chinese patent CN111231046A discloses a method for preparing a nut compaction board based on high-frequency technology. The nut compaction board has excellent processing performance and moisture resistance, and retains the inherent fragrance of nuts. The compaction board and its preparation method, the mixture made of nut crushed materials and PVB resin particles, and the PVB intermediate film are prepared through the pre-pressing body preparation step, the heating and pressurizing treatment step, and the cutting and polishing. When PVB resin fiber particles and PVB intermediate film are mixed and used under appropriate high-frequency hot pressing conditions, they have better water absorption thickness expansion rate performance. However, due to the use of PVB intermediate film, the paving time is usually long, and large-scale production has high equipment requirements. Chinese patent CN111300558A discloses a method for preparing a compacted wood fireproof board based on high-frequency technology, which is pressed by pre-treated wooden boards and a first flame retardant film, a second flame retardant film and a third flame retardant film made of different flame retardant formulations. Since this method uses wooden boards as raw materials and the cost of flame retardant films is relatively high, it is not suitable for preparing hot-pressed wood chips. Chinese patent CN109834776A discloses a compacted wood chip material and method based on high-frequency glue-free compaction technology, which uses dry resin particle mixing, resin film paving, and two hot pressing compaction steps to prepare laboratory-scale wood chip multilayer boards. The patented compacted wood chip material includes a wooden board layer and a compacted wood chip layer, and the stacking step requires an artificial PVB intermediate film, which makes automated production difficult. Therefore, there is still a need in the prior art for a compacted wood fiber board that can be mass-produced and has excellent physical properties and fire retardant properties. Summary of the invention

[0003] In view of the above technical problems, the present invention provides a variety of crushed wood fiber compressed boards and a quantitative production method of crushed wood fiber compressed boards. The main technical solutions are as follows:

[0004] The first aspect of the present invention provides a method for quantitatively producing a compressed wood fiber board, which comprises the following steps:

[0005] Mixing step: 55-80 parts by weight of wood fiber powder and 40-60 parts by weight of lime milk are mixed to obtain a primary wood fiber mixture, and the primary wood fiber mixture is mixed with 8-12 parts by weight of resin particles to obtain a secondary wood fiber mixture;

[0006] Molding step: placing the secondary wood fiber mixture in a mold for molding, and obtaining a wood fiber prefabricated board after demoulding;

[0007] Compressing step: subjecting the prefabricated wood fiber board to high-frequency heating and pressurization to obtain a semi-finished wood fiber compacted board;

[0008] Finishing step: subjecting the semi-finished product of the crushed wood fiber compacted board to cooling and curing treatment to obtain the crushed wood fiber compacted board.

[0009] The second aspect of the invention provides a method for quantitatively producing a compressed wood fiber board with flame retardant properties, which differs from the production method of the first aspect in that in the mixing step: after obtaining the primary wood fiber mixture, the primary wood fiber mixture is mixed with 8-12 parts by weight of resin particles, 20-40 parts by weight of magnesium oxide and 3-5 parts by weight of magnesium chloride to obtain a secondary wood fiber mixture.

[0010] The beneficial effects of the present invention are as follows: First, in the mixing step of the quantitative production method of the crushed wood fiber compacted board, the dry mixing method of the prior art is changed to a wet mixing method of first mixing lime milk and crushed wood fiber powder, and then adding resin particles, omitting the resin film, and performing three heating and pressurizing treatments in the compacting step, limiting the moisture content and the processing time after each heating and pressurizing. After comparison, the physical properties of the mass-produced board and the laboratory board are close. Secondly, the crushed wood fiber compacted board with balanced physical properties can be produced quantitatively, especially the uniformity of the nail holding force of the prepared board is significantly improved. Finally, by adding magnesium oxide, magnesium chloride and other technologies after the primary crushed wood fiber mixture, the synergistic flame retardant effect of the magnesium-based flame retardant and the inorganic adhesive is achieved, so that the flame retardant properties of the crushed wood fiber compacted board are significantly improved. DETAILED DESCRIPTION

[0011] The following examples further illustrate the content of the present invention, but should not be construed as limiting the present invention. Without departing from the spirit and essence of the present invention, modifications or substitutions made to the methods, steps or conditions of the present invention all fall within the scope of the present invention.

[0012] The preparation method of the compressed wood fiber board proposed in some embodiments of the present invention includes: a mixing step, a molding step, a compression step, and a finishing step.

[0013] Mixing steps

[0014] The mixing step of the present invention is to mix and stir the crushed wood fiber powder with auxiliary materials to finally prepare the crushed wood fiber mixed material.

[0015] The wood fiber powder of the present invention is obtained by grinding and crushing low-quality wood, fruit tree branches and buds into wood fiber fine powder with a mesh size of 180 mesh (particle size of about 0.088 μm) to 300 mesh (particle size of about 50 μm) through a wood fiber crusher. The types of the wood fiber crusher include but are not limited to flail type, drip type, ball mill, column mill, rod mill, tube mill, autogenous mill, mortar roller mill, vertical mill, multi-layer vertical mill, vertical roller mill, disc mill, DMC mill, etc. The low-quality wood includes fast-growing wood such as poplar, eucalyptus, fir, willow, etc. The fir includes Cryptomeria fortunei, Metasequoia, spruce, etc. The fruit tree branches include growing branches, fruiting branches and fruiting mother branches of apple, pear and peach. Equipment for processing wood chips may also include but is not limited to wood crushers, wood shredders, etc. Equipment for mixing wood fiber powder and auxiliary materials includes but is not limited to blenders, mixers, etc. The power of the mixer is 40-45KW, and the mixing is performed at 25 rpm. The mixing time is not specifically limited and can be determined according to the actual mixing conditions.

[0016] The resin of the present invention includes any one or more of ethylene-vinyl acetate copolymer (EVA) or polyolefin materials; the polyolefin material is any one or a mixture of at least two of polyethylene, polypropylene, modified polyethylene, modified polypropylene or ethylene elastomer containing ethylene units. The modified polyethylene includes polyvinyl butyral resin (PVB), polyvinyl chloride resin (PVC), polyvinyl formal (PVF), and the polyvinyl butyral resin (PVB) includes but is not limited to the production of Shanghai Meibang Plastic Co., Ltd. The particle size of the resin particles of the present invention is 0.03-0.05mm.

[0017] The flame retardant of the present invention includes one or more of phosphorus flame retardants, metal compound flame retardants, nitrogen flame retardants, boron flame retardants, nitrogen-phosphorus flame retardants, and magnesium flame retardants. The phosphorus flame retardant includes an organic phosphorus flame retardant and an inorganic phosphorus flame retardant, and the organic phosphorus flame retardant includes pentaerythritol phosphate (PEPA), di(2,6,7-trioxa-1-oxyphosphabicyclo[2.2.2]octane-4-methylene) phosphate melamine salt, di(2,6,7-trioxa-1-oxyphosphabicyclo[2.2.2]octane-4-methylene)-pentabromobenzyl phosphate, 2,4,6-tribromophenyl di(2,6,7-trioxa-1-oxyphosphabicyclo[2.2.2]octane-4-methylene) phosphate, and the inorganic phosphorus flame retardant includes one or more of diammonium phosphate, ammonium polyphosphate, guanidine nitrogen phosphate, and diammonium hydrogen phosphate. The magnesium flame retardant includes one or more of magnesium hydroxide, light-burned magnesium oxide (magnesia), magnesium chloride and magnesium chloride hexahydrate (halogen flakes), and the magnesium hydroxide includes nano-magnesium hydroxide fiber, nano-magnesium hydroxide flakes, and nano-magnesium hydroxide polyhedrons. Among them, magnesium chloride and magnesium chloride hexahydrate (halogen flakes) are also used as curing agents.

[0018] The lime milk of the present invention refers to a suspension of 15-25% calcium hydroxide. The preparation method of the lime milk of the present invention is a well-known technology. For example, water can be added to quicklime (calcium oxide) to generate a suspension of calcium hydroxide. In the present invention, the lime milk serves as an inorganic adhesive and also as a flame retardant accelerator due to a double replacement reaction with magnesium chloride to generate magnesium hydroxide. The reaction principle is Ca(OH)2+MgCl2→CaCl2+Mg(OH)2.

[0019] The flame retardant, curing agent, lime milk (or quicklime) and other auxiliary materials of the present invention need to be sieved through 100-240 meshes before feeding, so as to remove large particles of impurities.

[0020] The device used for mixing materials in the mixing step includes but is not limited to a stirrer or a mixer.

[0021] Molding steps

[0022] The molding steps of the present invention can be placing a mold frame on a hot press plate, unloading the secondary wood fiber mixture into the mold frame, locking the mold, and using a hot press to perform pre-pressing treatment after the shape is stable to obtain a wood fiber prefabricated board with a moisture content of 35%-40%. The molding steps of the present invention can be placing a mold frame on a hot press plate, unloading the secondary wood fiber mixture into the mold frame, locking the mold, and using a hot press to perform pre-pressing treatment after the shape is stable to obtain a wood fiber prefabricated board with a moisture content of 35%-40%.

[0023] The material conveying device includes, but is not limited to, a conveyor belt or a conveying pipe connected to the discharge port of the stirrer or mixer.

[0024] In a further embodiment of the forming step, the obtained wood fiber prefabricated board can also be subjected to an edge trimming step or an edge polishing step, the trimming equipment includes but is not limited to a cutter, and the polishing equipment includes but is not limited to a grinder, so that the edge of the wood fiber prefabricated board is more neat after trimming.

[0025] Compression steps

[0026] The compaction step of the present invention is to heat and pressurize the obtained wood fiber prefabricated board to obtain a wood fiber compacted board semi-finished product. The compaction method is a variety of hot pressing methods under high frequency conditions cited in Chinese patents CN109834776A, CN111300558A, and CN111231046A.

[0027] The equipment used in the compaction process is a compaction machine, which heats and pressurizes the prefabricated wood fiber board through the compaction machine. The compaction machine can be used to heat and pressurize the prefabricated wood fiber board once or multiple times under the same or different conditions to form a compacted wood fiber board semi-finished product, or it can be used to heat and pressurize the prefabricated wood fiber board once or multiple times and then use high-frequency heating to form a compacted wood fiber board semi-finished product. The compaction equipment is fully cited in Chinese patents CN109454721A, CN211221135U, CN111196407A, CN210100243U, CN109808013A, CN209453742U, and CN115781855A.

[0028] Finishing steps

[0029] The finishing step of the present invention is to subject the semi-finished product of the crushed wood fiber compacted board to a cooling and curing treatment to obtain the finished product of the crushed wood fiber compacted board.

[0030] A curing area is set up for the finished product of the wood fiber compacted board. The curing area is a space area that is ventilated, dry, maintains room temperature, and avoids external interference such as sunlight and rain. The curing space is a room of 10-20 square meters. In the curing area, a certain space is separated between the surfaces of each finished product of the wood fiber compacted board. The temperature in the curing area is 28-35°C, and the humidity is controlled at 5%. The surface of the wood fiber compacted board is cooled to 50°C and transferred to the curing space for 7-15 days. A ventilation system is set in the room to ventilate the curing space. Temperature and humidity monitoring equipment are set in the room to monitor the temperature and humidity of the curing space.

[0031] The method for preparing the compressed wood fiber board proposed in the embodiment of the present invention takes the "four-eight-foot" compressed wood fiber board (four feet (1220 mm) wide and eight feet (2440 mm) long) as an example. The quantitative production efficiency of the compressed wood fiber board on an assembly line can reach more than 30 cubic meters per hour. If the compressed wood fiber board is 12 mm thick, about 840 sheets of compressed wood fiber board can be produced per hour.

[0032] The compressed wood fiber board of the present invention can be used as a substrate, with a decorative layer attached to the surface.

[0033] The present invention is further described below with reference to specific embodiments. The "parts" in the specific embodiments all represent "parts by weight", which are converted after taking materials according to weight units such as kilograms (KG).

[0034] Example 1

[0035] Material preparation: 55 parts of poplar fiber powder, 40 parts of lime milk, 8 parts of PVB particles, where the lime milk is a suspension of 15% calcium hydroxide;

[0036] (1) Mixing steps

[0037] Primary wood fiber mixture: 55 parts of poplar fiber powder and 40 parts of lime milk are pre-mixed to form a primary wood fiber mixture, and then the primary wood fiber mixture is mixed with 8 parts of PVB particles to obtain a secondary wood fiber mixture, and then the material is transported to the compactor through a material conveying pipeline. PVB is granular, the particle size of PVB particles is 0.03mm, and the mesh number of poplar fiber powder is 180 mesh.

[0038] (2) Molding steps

[0039] The secondary wood fiber mixture is placed in a mold for locking, and demoulding is performed after pre-pressing to obtain a wood fiber prefabricated board with a moisture content of 35%.

[0040] (3) Compression step

[0041] The chipped wood fiber prefabricated board is subjected to a first heating and pressurizing treatment to obtain a first heating and pressurizing chipped wood fiber prefabricated board with a moisture content of 29%, the first heating and pressurizing treatment having a treatment temperature of 80° C., a treatment time of 2 minutes, and a first compression ratio of 40%;

[0042] The first heat-pressed wood fiber prefabricated board is subjected to a second heat-pressed treatment to obtain a second heat-pressed wood fiber prefabricated board with a moisture content of 15%, wherein the second heat-pressed treatment temperature is 90° C., the treatment time is 2 min, and the second compression ratio is 50%;

[0043] The second heat-pressed wood fiber prefabricated board is subjected to a third heat-pressed treatment to obtain a third heat-pressed wood fiber prefabricated board with a moisture content of 8%, wherein the third heat-pressed wood fiber prefabricated board is a semi-finished wood fiber compacted board. The third heat-pressed treatment temperature is 150° C., the treatment time is 2 minutes, and the third compression ratio is 65%;

[0044] (4) Sorting steps

[0045] The semi-finished wood fiber compacted board after the cooling treatment is placed in the health-preserving space for 15 days to obtain the wood fiber compacted board.

[0046] Embodiment 2-4

[0047] Embodiment 2-4 provides a method for preparing a compressed wood fiber board, which includes all the steps of Embodiment 1, and differs therefrom in the parameters shown in Table 1;

[0048] Table 1: Parameters of dosage of each component of Examples 2-4 different from Example 1

[0049]

[0050] Embodiment 5-7

[0051] Embodiment 5-7 provides a method for preparing a compressed wood fiber board, which includes all the steps of Embodiment 2, and the difference therefrom lies in the compression step, as shown in Table 2.

[0052] Table 2: Parameters of dosage of each component of Examples 5-7 different from Example 2

[0053]

[0054]

[0055] Comparative Example 1

[0056] The mixing step is to mix 55 parts of poplar fiber powder, 40 parts of lime milk, and 8 parts of PVB particles at the same time. The mixing time is the same as the sum of the two mixing times in Example 6, and the obtained wood fiber mixture is stirred only once. The other quantitative production methods of wood fiber compacted boards are the same as those in Example 6.

[0057] Comparative Example 2

[0058] The method of Example 12 in Chinese patent CN109834776A is adopted to lay wood chips and PVB intermediate film between two adjacent wooden boards, the mass ratio of the wooden board to the wood chips is 1:1, and the wood chips particle size is 5 cm, to obtain a laminated wooden board, and then the laminated wooden board is subjected to high-frequency heating and pressurization treatment to obtain a sandwich wood chip compacted board (including a wooden board layer-a wood chip block layer-a wooden board layer), and the two wooden board layers of the sandwich wood chip compacted board are cut off to obtain a wood chip compacted board.

[0059] Comparative Example 3

[0060] The compaction process of Comparative Example 3 is shown in Table 3. The quantitative production method of the compacted wood fiber board (not shown) is the same as that of Example 6.

[0061] Table 3: Comparative Example 3 Compacting Step Conditions

[0062]

[0063] Test Example 1: Plate surface density uniformity test

[0064] Purpose of the Test: Prepare the compressed wood fiber boards of the test examples according to the methods of Examples 1-7, compare them with the compressed wood (fiber) boards of the control examples prepared according to the preparation methods of Control Examples 1-3, and test the uniformity of the board surface density.

[0065] Test method: Take the wood (fiber) compacted boards prepared according to the preparation methods of Examples 1-7 and Control Examples 1-3, respectively. The length, width and height of each group of samples are the same, that is, 1220mm*2440mm*12mm. The density of different areas of the edge (5 test points on the short side, 10 test points on the long side, a total of 30 edge test points) and the middle (15 middle test points distributed in a matrix in the middle) of the board surface (the surface in the length direction and the width direction) of the same board are tested to obtain the density deviation of each part of the board. For other test methods, refer to the test methods in the national standard: "Test methods for physical and chemical properties of artificial boards and veneer artificial boards"-GB / T 17657-2013 for testing. The measurement results are shown in Table 4.

[0066] Table 4: Test results of surface density uniformity of compressed wood fiber board

[0067]

[0068]

[0069] Note: RSD = SD / X, where SD represents standard deviation and X represents mean value.

[0070] The test results show: First, the test results of the board surface density uniformity of Examples 1-7 show that in the preparation method of Examples 1-7, the wood fiber powder and lime milk are mixed in a certain ratio in advance, and finally a wet material compaction process is adopted, and the particle size of the wood fiber powder is relatively small. After the density uniformity test, the density difference between the board surface and the edge of the board is small, and the difference between the maximum density of the board surface and the minimum density of the edge of the board is small. It can be explained that the mixing process of the primary wood fiber mixture and the adjustment of the ratio between the wood fiber powder and lime milk or the mesh size of the wood fiber powder can affect the density uniformity of the board surface. Secondly, by comparing the test results of Examples 1-7 with those of Control Example 1, it can be seen that the wood fiber mixture of Control Example 1, which is stirred only once, will affect the uniformity of the board surface density even if the stirring time is extended to the same as the two stirring times of Example 6. Assuming that the stirring time is further extended to improve the uniformity of the board surface density, it will affect the quantitative production efficiency; the primary wood fiber mixture of Examples 1-7 can make the distribution of PVB particles more uniform, and thus have excellent uniformity of board surface density. Thirdly, by comparing the test results of Examples 1-7 with those of Control Example 2, it can be seen that Control Example 2 only uses PVB intermediate film and wood chips (wood chips with a particle size of 5 cm) that have not been ground and pulverized, which also makes the board surface density uniformity slightly worse than that of Examples 1-7. Moreover, Examples 1-7 use a more quantitative production technology that is more in line with the production line, and lime milk is used as an inorganic adhesive, which has a cost advantage. Fourthly, by comparing the test results of Examples 1-7 with those of Control Example 3, it can be seen that Control Example 3 adjusted the relevant parameters of the three high-frequency heating temperatures, processing time and moisture content of the wood fiber prefabricated board obtained after each pressurization in the compaction step. It can be seen that the effect of the uniformity of the board surface density is not as good as that of Examples 1-7. Finally, by comparing Examples 1-2 and Examples 5-7, which all use poplar fiber powder, it can be seen that the compaction step also has a certain influence on the uniformity of the board surface density.

[0071] Test Example 2: Plate cross-sectional density uniformity test

[0072] Purpose of the Test: Prepare the compressed wood fiber boards of the test examples according to the methods of Examples 1-7, compare them with the compressed wood (fiber) boards of the control examples prepared according to the preparation methods of Control Examples 1-3, and test the cross-sectional density uniformity of the boards.

[0073] Test method: The compressed wood fiber boards prepared according to the preparation methods of Examples 1-7 and Comparative Examples 1-3 were taken, and the length, width and height of each group of samples were the same, that is, 1220 mm*2440 mm*12 mm. The specific test method was tested in accordance with the test method in the Forestry Industry Standard of the People's Republic of China: "Method for Determination of Sectional Density of Artificial Boards"-LY / T 2718-2016. The test results are shown in Table 5;

[0074] Table 5: Test results of cross-sectional density uniformity of compressed wood fiber board (unit: g / cm 3 )

[0075]

[0076]

[0077] The test results show that: first, the test results of the cross-sectional density uniformity of Examples 1-7 show that the crushed wood fiber compacted board prepared by the mixing step, forming step, compacting step and curing step of the preparation method of Examples 1-7 has excellent cross-sectional density uniformity. Secondly, by comparing the test results of Examples 1-7 with those of Reference Examples 1 and 3, it can be seen that the mixing step of Reference Example 1 and the compacting step of Reference Example 3 may affect the cross-sectional density uniformity. In addition, compared with Reference Example 2, although Reference Example 2 shows that the RSD of the density uniformity of each layer (including the wooden board layer-crushed wood block layer-wood board layer) is only 0.017, after comparing the cross-sectional density uniformity test of the crushed wood block layer alone, the comparison result is not as good as that of Example 1-7. Finally, by comparing Examples 1-2 and Examples 5-7, both of which use poplar fiber powder, it can be seen that the conditions of the compacting step have a certain influence on the cross-sectional density uniformity of the board.

[0078] Embodiment 8-10

[0079] Examples 8-10 provide a method for preparing a wood fiber compacted board with flame retardant properties (also known as a fireproof wood fiber compacted board), which includes all the steps of Example 6, except that lightly burned magnesium oxide and magnesium chloride are added to the primary wood fiber mixture material, and the mixture is mixed to obtain a secondary wood fiber mixture, and the specific amount is as shown in Table 6.

[0080] Table 6: Parameters of dosage of each component of Examples 8-10 different from Example 6

[0081] project Example 8 Example 9 Example 10 Magnesium chloride 3 servings 4 servings 5 servings Magnesium chloride fineness 180 mesh 200 mesh 240 mesh Magnesium Oxide 20 servings 30 servings 40 servings Magnesium oxide fineness 180 mesh 200 mesh 240 mesh

[0082] Embodiment 11

[0083] This embodiment provides a wood fiber compact board with flame retardant properties. The quantitative production method of the wood fiber compact board includes all the steps of Example 8, except that 55 parts of lime milk and 5 parts of magnesium chloride hexahydrate (halogen flakes) are used.

[0084] Example 12

[0085] This embodiment provides a compressed wood fiber board. The quantitative production method of the compressed wood fiber board includes all the steps of Example 8, except that 60 parts of lime milk and 5 parts of magnesium chloride hexahydrate (halogen flakes) (240 mesh) are used.

[0086] Comparative Example 4

[0087] In the mixing step, 3 parts of aluminum sol, 5 parts of water glass and 8 parts of deionized water are used instead of lime milk. The other quantitative production methods of the wood fiber compacted board are the same as those in Example 9.

[0088] Comparative Example 5-6

[0089] The compaction steps of Comparative Examples 5-6 are shown in Table 7, and other parameters not shown are the same as those of Example 9;

[0090] Table 7: Comparative Example 5-6 Compacting Step Conditions

[0091]

[0092]

[0093] Comparative Example 7

[0094] In the mixing step, polyvinyl alcohol is used instead of PVB particles. Other quantitative production methods of the wood fiber compacted board are the same as those in Example 9.

[0095] Comparative Example 8

[0096] The method of Example 2 in Chinese Patent CN1094351A is adopted, wherein;

[0097] Mixing steps: 4 kg of magnesium chloride is adjusted to 28 degrees Baume with water, 4 kg of crushed hydrocolloid is boiled and dissolved in water, 3 kg of slaked lime, 3 kg of sugar and water equal to the slaked lime are heated and boiled, stirred and allowed to stand for 4 days, 8 kg of magnesium oxide and 23 kg of straw scraps are mixed, and the above-prepared materials are steam-heated and stirred;

[0098] Molding steps: when heated to 80°C, put it into a mold sprinkled with waterproof and heat-insulating powder. During the process, bamboo reinforcements are laid vertically and horizontally in layers, and waterproof and heat-insulating powder is sprinkled on the surface of the material.

[0099] Compacting steps: After vibration, use a hydraulic press with 30kg / cm 2 to suppress;

[0100] Finishing steps: heat preservation and curing, demoulding and drying.

[0101] Test Example 3: Plate surface density uniformity test

[0102] Referring to the method of Test Example 1, the crushed wood fiber compressed boards of the test examples were prepared according to the methods of Examples 8-10, and the uniformity of the board surface density of the boards was tested. The measurement results are shown in Table 8.

[0103] Table 8: Test results of density uniformity in different areas of the compressed wood fiber board of Examples 8-10

[0104]

[0105] The test results show that: according to the test results of the board surface density uniformity of Examples 8-10, the preparation method of Examples 8-10 also adopts the method of pre-mixing the crushed wood fiber powder and lime milk according to a certain ratio, and finally adopts the wet material compaction process, and the particle size of the crushed wood fiber powder is relatively small. After the density uniformity test, the density difference between the board surface and the edge of the board is small, and the difference between the maximum density of the board surface and the minimum density of the edge of the board is small. While ensuring its flame retardant effect, Examples 8-10 are slightly inferior to Examples 5-7, but compared with other comparative examples, they still have obvious advantages in terms of density uniformity of the board.

[0106] Test Example 4: Plate cross-section density uniformity test

[0107] Referring to the method of Test Example 2, the crushed wood fiber compressed boards of the test examples were prepared according to the methods of Examples 8-10, and the cross-sectional density uniformity of the boards was tested. The test results are shown in Table 9;

[0108] Table 9: Test results of cross-sectional density uniformity of compressed wood fiber board (unit: g / cm 3 )

[0109]

[0110] The test results show that:

[0111] The test results of the cross-sectional density uniformity of the boards of Examples 8-10 show that Examples 8-10 have excellent cross-sectional density uniformity, and the density of the boards is more uniform while taking into account the flame retardant properties, indicating that the structure is stable.

[0112] Test Example 5: Combustion test of wood fiber compressed board

[0113] The crushed wood fiber compacted board was prepared by the preparation methods of Examples 8-12 and Comparative Example 4, and a combustion test was carried out according to the method specified in GB8624-2012. The test results are shown in Table 10:

[0114] Table 10: Burning test results of wood fiber compressed board

[0115] project PCS <![CDATA[FIGRA 0.2MJ ]]> Flame spread horizontally <![CDATA[THR 600s ]]> Example 8 2.5 33 Does not reach the edge of the style long wing 3.5 Example 9 2.3 29 Does not reach the edge of the style long wing 2.8 Example 10 2.6 35 Does not reach the edge of the style long wing 3.7 Embodiment 11 2.8 45 Does not reach the edge of the pattern long wing 4.2 Example 12 2.6 50 Does not reach the edge of the style long wing 4.3 Comparative Example 4 4.3 117 Does not reach the edge of the style long wing 8.7

[0116] Note: PCS means total calorific value, FIGRA 0.2MJ Indicates the burning growth rate index, THR 600s Indicates the total heat released within 600s.

[0117] Analysis of test results: Examples 8-12 all meet the Class A standard specified in GB8624-2012, among which the combustion performance of the wood fiber board prepared by the preparation method of Example 9 is closer to Class A1, while the test results of Control Example 4 show that some indicators of the combustion performance of the board fail to reach Class A. Compared with Examples 8-12, Control Example 4 uses 3 parts of aluminum sol, 5 parts of water glass, and 8 parts of deionized water instead of lime milk as an inorganic adhesive. From the comparison results, the combustion performance of the board is affected, which also shows that the application selects lime milk not simply as an adhesive. Examples 8-10 adjust the proportion and concentration of lime milk and its addition in combination with different ratios of magnesium chloride and magnesium oxide to become conditions that affect the combustion performance of the board.

[0118] Test Example 6: Test on uniformity of screw holding force in different areas and screw holding force in different batches

[0119] The crushed wood fiber compressed board was prepared according to the method of Examples 8-10, and compared with the crushed wood fiber compressed board of the control example prepared according to the preparation method of Control Examples 5-6. The length, width and height of the crushed wood fiber compressed board prepared according to the methods in Examples 8-10 and Control Examples 5-6 for the test were the same, i.e., 1220mm*2440mm*12mm. Three batches of boards were prepared by each method, and the uniformity of the screw holding force in different areas of the same board was measured, and the stability of the screw holding force was tested on boards of different batches, so as to determine whether the deviation of the screw holding force at different positions of the same board is too large and whether the screw force of boards of different batches using the same method is stable. For specific test methods, refer to the national standard: "Test methods for physical and chemical properties of wood-based panels and veneered wood-based panels" - GB / T 17657-2013 for testing, and the test results are shown in Table 11.

[0120] Table 11: Test results of uniformity of screw holding force in different areas of wood fiber compacted board

[0121]

[0122] The test results show that: Examples 8-10 and Control Examples 5-6 all use three high-frequency heating and pressurizing process steps. Compared with Control Examples 5-6, the difference is that Examples 8-10 use different high-frequency heating temperatures and treatment times. After comparison, it can be found that the difference in screw holding force between the edge and the surface of the same board of the wood fiber compressed board prepared according to Examples 8-10 is smaller, the nail holding force at various positions on the board surface is more uniform and stable, and the nail holding force of both the board surface and the board edge is stronger than that of Control Examples 5-6, which is more suitable for industrial mass production. This shows that adjusting the high-frequency heating temperature and treatment time can affect one of the indicators of the uniformity of the screw holding force of the wood fiber compressed board.

[0123] Experimental Example 7 Formaldehyde Emissions

[0124] According to the preparation method of Example 9, a group of wood fiber compacted boards for the experiment were prepared. The length, width and height of the boards of the test groups 1-3 were 2m*1.2m*0.5m respectively. The particle boards of the same area were purchased from Shandong Linyi Hongze Board Factory. The test group 1 and the particle board were placed on a 10m 2 The temperature was adjusted to 60℃ in the room, and the wood was sealed and placed for 15 days. The formaldehyde emission in the wood was detected by formaldehyde detection instrument. The formaldehyde emission detection results of the wood in each test group are shown in Table 12.

[0125] Table 12: Test results of formaldehyde emission from test groups 1-3 and particleboard

[0126] Group No. wood <![CDATA[Formaldehyde emission (mg / m 3 )]]> Experimental Group 1 Poplar none Particle Board / 0.13

[0127] Test results: The flame-retardant wood fiber compacted board prepared by the preparation method of the present invention has no formaldehyde emission.

[0128] Test Example 8 Physical Properties Test

[0129] The compressed wood fiber boards prepared by the preparation methods of Examples 8-10 and Comparative Examples 7 and 8 were subjected to physical property tests in accordance with the National Standard of the People's Republic of China GB / T 17657-2013 Test Methods for Physical and Chemical Properties of Artificial Boards and Veneer Artificial Boards. The test results are shown in Table 13.

[0130] Table 13: Comparison of physical properties test results

[0131]

[0132] The results show that the physical properties of the compressed wood fiber boards of Examples 8-10 are better than those of Comparative Examples 7 and 8, and the physical properties of the compressed wood fiber boards prepared by the preparation method of Example 9 are better than those of Comparative Examples 7 and 8 and the preparation methods of other Examples;

[0133] Compared with the control example 7, the polyvinyl alcohol in the embodiment 9 is replaced by PVB particles. The test results show that at least the static bending strength and load indexes thereof are enhanced. Therefore, it is proved that the use of PVB particles and the corresponding adjustment of their particle size may have an impact on some physical properties of the board.

[0134] Compared with Control Example 8, Examples 8-10 are also fireproof panels and use some of the same components, but there are differences in the preparation methods. For example, the preparation method of Example 9 adopts the method of first preparing a primary wood fiber mixture, controlling the ratio of wood fiber powder to lime powder, the concentration of lime powder, optimizing the mesh size of wood fiber powder, the particle size of PVB, the ratio of magnesium oxide to magnesium chloride added, the fineness of magnesium oxide powder and magnesium chloride powder, and further controlling the conditions of high-frequency heating and pressurization. The method used in Control Example 8 is to melt the water glue, boil slaked lime in water, let it stand for 3-4 days, mix it with magnesium oxide and sawdust, heat, press, insulate and cure, cool and finally demold and dry. Although the process is simple and low in cost as described, some of its physical properties are still reduced compared with Examples 8-10.

[0135] The above-described embodiments are merely descriptions of preferred implementation modes of the present invention and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A quantitative production method of compressed wood fiber board, characterized in that: The method comprises the following steps: Mixing step: 55-80 parts by weight of wood fiber powder and 40-60 parts by weight of lime milk are mixed to obtain a primary wood fiber mixture, and the primary wood fiber mixture is mixed with 8-12 parts by weight of resin particles to obtain a secondary wood fiber mixture; Molding step: placing the secondary wood fiber mixture in a mold for molding, and obtaining a wood fiber prefabricated board after demoulding; Compressing step: subjecting the prefabricated wood fiber board to high-frequency heating and pressurization to obtain a semi-finished wood fiber compacted board; Finishing step: subjecting the semi-finished product of the crushed wood fiber compacted board to cooling and curing treatment to obtain the crushed wood fiber compacted board.

2. The method according to claim 1, characterized in that In the mixing step: after obtaining the primary wood fiber mixture, the primary wood fiber mixture is mixed with 8-12 parts by weight of resin particles, 20-40 parts by weight of magnesium oxide and 3-5 parts by weight of magnesium chloride to obtain a secondary wood fiber mixture.

3. The method according to any one of claims 1 to 2, characterized in that: The mesh number of the crushed wood fiber powder is 180-300 meshes; the lime milk, the magnesium oxide and the magnesium chloride are respectively passed through a 100-240 mesh sieve before being added.

4. The method according to any one of claims 1 to 2, characterized in that: The particle size of the resin particles is 0.03-0.05 mm.

5. The method according to any one of claims 1 to 2, characterized in that: The resin includes any one or more of ethylene-vinyl acetate copolymers or polyolefin materials; the polyolefin material is any one or a mixture of at least two of polyethylene, polypropylene, modified polyethylene, modified polypropylene or ethylene elastomers containing ethylene units; the modified polyethylene includes polyvinyl butyral resin (PVB), polyvinyl chloride resin (PVC), and polyvinyl formal (PVF).

6. The method according to any one of claims 1 to 2, characterized in that: In the molding step: the secondary wood fiber mixture is pre-pressed before or after demolding to obtain a wood fiber prefabricated board with a moisture content of 35%-40%.

7. The method according to any one of claims 1 to 2, characterized in that: The compacting step comprises: The wood fiber prefabricated board is subjected to a first heating and pressurizing treatment to obtain a first heating and pressurizing treated wood fiber prefabricated board having a moisture content of 29%-32%, wherein the treatment temperature of the first heating and pressurizing treatment is 80-90° C. and the treatment time is 1-10 min; The first heat-pressed wood fiber prefabricated board is subjected to a second heat-pressed treatment to obtain a second heat-pressed wood fiber prefabricated board having a moisture content of 15%-19%, wherein the second heat-pressed treatment is performed at a temperature of 90-100° C. and for a time of 1-5 min; The wood fiber prefabricated board subjected to the second heating and pressurizing treatment is subjected to the third heating and pressurizing treatment to obtain the wood fiber prefabricated board subjected to the third heating and pressurizing treatment with a moisture content of 8%-15%. The wood fiber prefabricated board subjected to the third heating and pressurizing treatment is the semi-finished wood fiber compacted board. The treatment temperature of the third heating and pressurizing treatment is 150-180°C and the treatment time is 1-3min.

8. The method according to claim 7, characterized in that In the compaction step: the first compression ratio is 35%-40%, the second compression ratio is 45%-55%, and the third compression ratio is 60%-70%.

9. The method according to any one of claims 1 to 2, characterized in that: The wood chip fiber powder comprises at least one of low-quality wood chip fiber powder and fruit tree branch bud fiber powder.

10. A compressed wood fiber board, characterized in that: The compressed wood fiber board is prepared according to the quantitative production method of any one of claims 1 to 9.

Citation Information

Patent Citations

  • Adhesive-free pressing and sealing equipment based on high frequency

    CN109454721A

  • High-frequency compacted wood combined production line

    CN109808013A

  • Device for uniformly discharging compressed moisture in surface of compacted wood and compacted wood device production line

    CN111196407A

  • Nut compacting plate based on high frequency technology and manufacturing method thereof

    CN111231046A

  • Compacted fireproof wooden board manufacturing method based on high frequency technology

    CN111300558A